Effect of herbal extract mixture on growth performance and antioxidant parameters in broilers - Ölmez, Mükremin; Şahin, Tarkan; Karadağoğlu, Özlem; Yörük, Mehmet Akif; Karadağ Sari, Ebru; Yediel Aras, Şükran; Öğün, Metin; Makav, Mustafa (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was conducted to determine the effects on the growth performance and antioxidant capacity of broiler chickens, which were fed an herbal extract mixture (HEM), including Honokiol-Magnolol and Sanguinarine as natural feed additives. A total of 300 one-day-old male Ross 308 broilers were used in this study and randomly divided into four groups with five replicates of 15 broiler chicks each. For the experimental groups, HEM was supplemented in their diet at the levels of 0.00% (C), 1.00% (HEM1), 1.50% (HEM2) and 2.00% (HEM3) respectively. At the end of the experiment, it was concluded that HEM influenced final body weight, body weight gain, feed consumption, feed conversion ratio, slaughter weight, carcass weight and carcass yield (P<0.05). Also, HEM decreased malondialdehyde level (P<0.05) and increased glutathione of the breast and liver tissues (P<0.05). HEM showed strong cytoplasmic manganese superoxide dismutase immunoreactivity in duodenal crypts. It is concluded that HEM supplementation to broiler diets may improve the growth performance and antioxidant parameters. Thus, HEM may use natural feed additives to improve broiler health and performance.